Training fields, competencies, education for… School curricula and disciplines in shake : The case of Sustainable development education - Audigier, François (Swiss Journal of Educational Research, 2018)
Educational subjects that knock on school’s door are more and more numerous: environment, entrepreneurship, information… These subjects are generally labelled Education to… In this article, I consider them as expressions of school attempts to adapt itself to the world when it comes to individual, worker and citizen education. Education to… demand to build more useful skills so that individuals can cope with the situations he will encounter during his personal, social, professional and civic life. They force us to redefine educational content and devices; they question the way teaching is organized into different school subjects. Education for sustainable development is particularly indicative of the tensions caused by these Education to…